The Effect of Technical Irrigation Systems and Agricultural Water Management on Rice Production Yields and Water Use Efficiency in Bogor - Dila Padila Nurhasanah; Eko Sutrisno; Sintia Permata Sari (West Science Agro, 2026)
Efficient irrigation systems and sustainable agricultural water management are essential factors in improving rice productivity and optimizing water resource utilization. This study aims to examine the effect of technical irrigation systems and agricultural water management on rice production yields and water use efficiency in Bogor. A quantitative research approach was applied using survey data collected from 100 rice farmers. Data were obtained through a structured questionnaire measured using a five-point Likert scale and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) version 3. The analysis consisted of measurement model evaluation, including validity and reliability testing, and structural model evaluation through path coefficient analysis, coefficient of determination (R²), predictive relevance (Q²), and hypothesis testing. The results indicate that technical irrigation systems have a positive and significant effect on rice production yields and water use efficiency. Furthermore, agricultural water management demonstrates a stronger positive influence on rice production yields and significantly improves water use efficiency. Rice production yields also positively contribute to water use efficiency. These findings indicate that irrigation infrastructure development should be integrated with effective water management practices to achieve higher agricultural productivity and sustainable water utilization. This study provides practical implications for farmers, agricultural institutions, and policymakers in developing more efficient rice production systems in Bogor.